Emergency nurses' experiences of the implementation of early goal directed fluid resuscitation therapy in the management of sepsis: a qualitative study. (March 2021) - Kabil, Gladis; Hatcher, Deborah; Alexandrou, Evan; McNally, Stephen
Abstract: Background: Severe sepsis can lead to organ failure and death if immediate treatment, such as intravenous fluids and antibiotics, are not commenced within the first hour. Time - critical initiation of intravenous fluids which in other words is early goal directed fluid resuscitation has not always been given its clinical priority. This qualitative study aimed at exploring the experiences of emergency nurses initiating early goal directed fluid resuscitation in patients with sepsis. Methods: Using an exploratory approach, face - to - face semi - structured interviews were conducted with ten registered nurses working in emergency departments across New South Wales, Australia. Thematic analysis was used for data analysis. Findings: Participants described various factors that inhibited the timely initiation of early goal directed fluid resuscitation, some clinical practice challenges, and strategies to improve nursing practice. Most participants, particularly those practicing as Clinical Initiatives Nurses suggested the incorporation of nurse initiated early goal directed fluid resuscitation for patients with sepsis as part of their scope of practice. Conclusion: Our findings identified several barriers that inhibit effective nurse - initiated early goal directed fluid resuscitation. It is anticipated that these findings will provide validation for the re-evaluation of the existing protocols and practice guidelines to increase the scope of practice of emergency nurses initiating early goal directed fluid resuscitation.